Validation of the Australian Treatment Outcomes Profile for use in clients with cannabis dependence. (4th March 2020) - Mills, Llewellyn; Lintzeris, Nicholas; Bruno, Raimondo; Montebello, Mark; Dunlop, Adrian; Deacon, Rachel M.; Copeland, Jan; Jefferies, Meryem; Rivas, Consuelo; Mammen, Kristie
Abstract: Introduction and Aims: The Australian Treatment Outcomes Profile (ATOP) was developed as a clinical tool for monitoring the substance use, health and wellbeing of clients in alcohol and other drug treatment. This is the first psychometric validation of the ATOP in a cannabis‐dependent treatment population. Design and Methods: A total of 128 individuals with cannabis dependence enrolled in an outpatient randomised controlled trial were administered the ATOP and gold‐standard health and wellbeing questionnaires once by clinicians and once by researchers at baseline. Concurrent validity was assessed by testing ATOP Psychological Health, Physical Health and Quality of Life questions against concurrently administered gold‐standard questionnaires: the Short Form 36 Health Survey (SF‐36), the 21‐item Depression, Anxiety and Stress Scale (DASS‐21) and the Sheehan Disability Scale (SDS). Interrater reliability was tested by comparing clinician‐administered ATOP items at the medical screening interview to the same ATOP items administered by researchers at baseline. Results: ATOP Psychological Health showed moderate to strong correlations with SF‐36 Mental Components, SF‐36 Mental Health and DASS‐21 scores ( r = 0.40–0.52) and ATOP Physical Health with SF‐36 Physical Components and SF‐36 General Health scores ( r = 0.36–0.67). The ATOP Quality of Life scale showed moderate agreement with the SDS and six‐dimensional health state short form scales ( r = 0.38–0.40). ATOP substance use, employment, education and child care items showed good to excellent interrater reliability (Krippendorff's α = 0.62–0.81), and tobacco use, Psychological Health, Physical Health and Quality of Life showed fair to moderate interrater reliability (Krippendorff's α = 0.42–0.53). Discussion and Conclusions: The ATOP appears to be valid and reliable when tested in a population with cannabis‐dependence, justifying its widespread use in clinical settings.